New sustainable materials from waste feathers: Properties of hot-pressed feather/cotton/bi-component fibre boards - Dieckmann,E; Eleftheriou,K; Audic,T; Lee,KY; Sheldrick,L; Cheeseman,C (Sustainable Materials and Technologies, 2019)
Feathers from poultry are an abundant, globally available waste. The current beneficial reuse for feathers involves autoclaving them to produce feather meal, an animal feed with low economic value. This paper reports on the production and performance of new feather-derived materials. These have potential to provide a higher value application for waste feathers. Feather fibres, cotton fibres and polyethylene/polypropylene bi-component fibres (blended 55:20:25 by weight) have been air-laid to form 20 mm thick non-woven pre-forms with a density of 0.14 g cm −2 . These were then hot pressed to produce materials with significantly higher density and improved properties. Optimum materials were formed by hot pressing between 150 and 160 °C at 6 MPa for 1 min. Lower temperatures resulted in poor fibre bonding and fibre pull-out during fracture. Higher temperatures caused thermal degradation of the feather fibres. The optimum feather fibre boards with a density of 0.77 g/cm 3 , corresponding to 31.3% porosity, had tensile strengths of 17.9 MPa a tensile modulus of 1.74 GPa and an elongation at fracture of 5.9%. These samples exhibited fibre fracture during tensile testing. Feather fibre boards have similar tensile strength, density and Young's modulus to particleboard, organic resin particleboard and flake board. Quantitative estimates of the economic and environmental benefits from using feather fibres to form feather fibre boards are discussed. The research advances sustainability by providing a new potential circular economy outlet for waste feathers and is part of on-going research to develop novel applications that exploit the unique properties of feathers.